2020
DOI: 10.2147/ott.s251295
|View full text |Cite
|
Sign up to set email alerts
|

<p>Inhibition of ERKs/Akt-Mediated c-Fos Expression Is Required for Piperlongumine-Induced Cyclin D1 Downregulation and Tumor Suppression in Colorectal Cancer Cells</p>

Abstract: Background: Deregulation of Cyclin D1 and cell cycle progression plays a critical role in tumorigenesis. The natural compound piperlongumine (PL) exhibits potential anticancer effects in various cancer models, but the underlying mechanism needs further elucidation. Methods: The inhibitory effect of PL on colorectal cancer (CRC) cells was determined by anchorage-dependent and-independent assays. The protein level of Cyclin D1 was examined by immunoblot (IB) and immunohistochemical staining (IHC). The mRNA level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…1 H, I). On the basis of these findings and in line with previous studies showing that PI3K/AKT and ERK1/2 transduction pathways mediate the expression of insulin target genes, such as c‐Fos and Cyclin D1 [ 27 , 44 46 ], we found that insulin induces c-Fos expression in BCAHC-1 cells at both mRNA (data not shown) and protein levels (Fig. 2 A–C).…”
Section: Resultssupporting
confidence: 91%
“…1 H, I). On the basis of these findings and in line with previous studies showing that PI3K/AKT and ERK1/2 transduction pathways mediate the expression of insulin target genes, such as c‐Fos and Cyclin D1 [ 27 , 44 46 ], we found that insulin induces c-Fos expression in BCAHC-1 cells at both mRNA (data not shown) and protein levels (Fig. 2 A–C).…”
Section: Resultssupporting
confidence: 91%
“…Similarly, a recent report has shown that PL could suppress tumor cell growth and proliferation in DMH/ DSS-induced experimental colon cancer by targeting Ras/PI3K/ Akt/mTOR signaling axis (Kumar and Agnihotri, 2019). PLinduced Cyclin D1 downregulation and tumor suppression in colorectal cancer cells by suppression of ERKs/Akt-mediated c-Fos expression (Gao et al, 2020). PL could also induce apoptosis by activation of JNK in colorectal cancer HCT116 cells independent of Bax, p21 and p53 status (Li et al, 2015;DA Silva Machado et al, 2018).…”
Section: Discussionmentioning
confidence: 84%
“…At this time, the mechanism through which exposure to PL downregulates Smad3 expression and upregulates NDRG1 expression remains to be elucidated. However, PL has been reported to inhibit extracellular signal-regulated kinase 1/2 activation in colorectal cancer cells (42). A similar effect in MDA-MB-231 cells may account for the reduced Smad3 expression, since the inhibition of extracellular signal-regulated kinase signaling suppresses Smad3 expression in epithelial cells (43).…”
Section: Discussionmentioning
confidence: 98%